Design and Methodology of a Multicenter Randomized Clinical Trial to Evaluate the Efficacy of Tongmai Jiangtang Capsules in Type 2 Diabetic Coronary Heart Disease Patients - Wang, Yu; Guo, Yilei; Lei, Ye; Huang, Shuwei; Dou, Liping; Li, Chang; Zhao, Buchang; Fu, Wei; Zhou, Peng; Wan, Haitong; Zhao, Mingjun; Yang, Jiehong (Frontiers in Pharmacology, 2021)
Background: Population-based studies have consistently showed an increased incidence of coronary heart disease and cardiac mortality in patients with type 2 diabetes mellitus (T2DM). Tongmai Jiangtang capsules (TJC) are Chinese patent medicines that have been approved in China for the treatment of diabetic vascular complications. However, the evidence supporting the efficacy of Tongmai Jiangtang capsules in type 2 diabetic coronary heart disease (T2DM-CHD) remains unclear. Herein, we designed a randomized, parallel-controlled clinical trial to investigate a new complementary therapy for T2DM-CHD patients. Methods: A total of 360 T2DM-CHD subjects (aged 18–75 years) will be randomly assigned to the TJC group or the placebo group at a 2:1 ratio. On the basis of western medicine therapy, all the participants will receive TJC or placebo, orally, three capsules/treatment, three per day for 12 weeks. The primary outcomes will be assessed according to the Canadian Cardiovascular Society (CCS) classification. All statistical analyses will be performed setting a two-sided 0.05 significance level, using SAS 9.4 statistical software. Discussion: The efficacy of TJC for the treatment of T2DM-CHD patients will be evaluated. The study will provide reliable clinical research evidence for application of TJC in treating T2DM-CHD patients. Clinical Trial Registration:https://www.chictr.org.cn/enIndex.aspx, Chinese Clinical Trial Registry ChiCTR2000037491.